Guru Padmasambhava and Nyingma school of Tibetan Buddhism (Bodhi Path, 2022)
Guru Padmasambhava is so far the most prominent among all the Nyingma teachers known to Tibetan Buddhism who is also known as “Guru Rinpoche”. Guru Rinpoche who perhaps lived during the 8th century has received his teachings from Jamphel She Nyen and Garap Dorje and his missionary works spread the lineage into Tibet. In Tibetan Buddhism he is considered as an emanation of the Buddha Amitabha by Nyingma school whose fastidious objective was to ease the propagation of Buddhism in the early period. The biography written by his disciple Yeshe Tsogyal states that many aspects of his early life closely similar to the life of the Buddha Shakyamuni. He took an extraordinary birth in a small north Indian kingdom. The popular legends embrace that he was born in the country of Oddiyana from the bud of a large and multicolored ‘Lotus’. The literal meaning of the name Padmasambhava means ‘born from a lotus’. The king of Indrabodhi was not having any son, so he adopted Padmasambhava as his son. The Padmasambhava also grew up in a palace like Buddha Shakyamuni and learned the arts and sciences suitable to princes. Although the king Indrabodhi wanted him to follow his footsteps as a king and take care of the kingdom. But Padmasambhava realized that being a king he would not be able to benefit others as much as he can through spreading the Buddha Dharma.
Keywords: Guru Padmasambhava; Nyingma school of Tibetan Buddhism